2021
DOI: 10.3390/ijms22073512
|View full text |Cite
|
Sign up to set email alerts
|

Yersiniabactin Siderophore of Crohn’s Disease-Associated Adherent-Invasive Escherichia coli Is Involved in Autophagy Activation in Host Cells

Abstract: Background: Adherent-invasive Escherichia coli (AIEC) have been implicated in the etiology of Crohn’s disease. The AIEC reference strain LF82 possesses a pathogenicity island similar to the high pathogenicity island of Yersinia spp., which encodes the yersiniabactin siderophore required for iron uptake and growth of the bacteria in iron-restricted environment. Here, we investigated the role of yersiniabactin during AIEC infection. Methods: Intestinal epithelial T84 cells and CEABAC10 transgenic mice were infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…It had been widely believed that the Th1 cell response was the main cause of CD. This idea was supported by experiments showing that Th1 cells produce TNF-α and IFN-γ, and IFN-γ can activate macrophages to produce additional TNF-α, leading to the apoptosis of epithelial cells and inducing CD[ 46 ]. Moreover, experiments have shown that many Th17 cells infiltrate the inflammatory gastrointestinal mucosa of IBD patients, and the upregulation of Th17 cell-secreted cytokine expression ( e.g.…”
Section: Aiec and Gut Immune Systemmentioning
confidence: 99%
“…It had been widely believed that the Th1 cell response was the main cause of CD. This idea was supported by experiments showing that Th1 cells produce TNF-α and IFN-γ, and IFN-γ can activate macrophages to produce additional TNF-α, leading to the apoptosis of epithelial cells and inducing CD[ 46 ]. Moreover, experiments have shown that many Th17 cells infiltrate the inflammatory gastrointestinal mucosa of IBD patients, and the upregulation of Th17 cell-secreted cytokine expression ( e.g.…”
Section: Aiec and Gut Immune Systemmentioning
confidence: 99%
“…However, our results showed that clinical C. freundii isolates with HPI do not exhibit higher pathogenicity than HPI-negative isolates ( Figure 4 ). The possible relevant mechanisms include (1) ICE may not exhibit its functions when bound to the host’s chromosome and only functions after it has been sheared down to form a loop ( Johnson and Grossman, 2015 ) and (2) HPI-containing strains activate host’s autophagy, making the HPI-carrying host at a disadvantage stage at certain point ( Dalmasso et al, 2021 ). From the perspective of virulence factors contained in the whole, through comparison of VFDB database, it was found that clade3 and clade4 had no difference in virulence factor except HPI gene cluster.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagosome then fuses with lysosome for the subsequent degradation of its content ( Klionsky et al., 2021 ). Our group has shown that upon AIEC infection, autophagy is induced in host cells, and a functional autophagy is necessary to limit the intracellular replication of AIEC ( Lapaquette et al., 2010 , 2012 ; Bretin et al., 2016 , 2018 ; Dalmasso et al., 2021 ). We also showed that while host cells induce a functional autophagy to eliminate AIEC, AIEC can subvert autophagy by up-regulating the levels of microRNAs 130a and 30c of host cells ( Nguyen et al., 2014 ) or by impairing host SUMOylation, a eukaryotic reversible post-translational modification, in which SUMO, a ubiquitin-like polypeptide, is covalently linked to target proteins ( Dalmasso et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%